Knowledge and Beliefs about the Use of Antibiotics in Society: A Questionnaire Study of Gorontalo Province, Indonesia - Rasdianah, Nur; Akuba, Juliyanty; Nurrohwinta Djuwarno, Endah (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
A lack of public understanding of the use of antibiotics has the potential to cause inappropriate use of antibiotics. The research aims to obtain information about the knowledge and beliefs of respondents regarding the use of antibiotics in Gorontalo Province.Methods: The study population is people over 18 years of age. Sampling was done randomly (N=384). Data was collected using a questionnaire and the results were analyzed using descriptive statistics.Results: Of the 384 respondents who met the inclusion and exclusion criteria, 55.99% of respondents knew that antibiotics had to be purchased with a doctor's prescription and that various types of antibiotics could be used for one type of bacterial infection (70.31%), antibiotics could be taken twice at the next dose (63.80%), accelerated recovery (60.16%), its use was stopped when symptoms disappeared (56.25%), the method of use was the same as other drugs (52.86) and effectively treated viruses (51.82). %), antibiotics can cause allergies (52.34%), resistance (59.38%), and bacterial resistance can increase if their use is not appropriate (48.96%). The results of the correlation analysis showed that there was a significant and unidirectional relationship between the two (rho=0.467).Conclusion: Respondents have adequate knowledge about antibiotics, resistance, and side effects but have inaccurate knowledge about the effectiveness of antibiotics for viral infections. Respondents have sufficient confidence that antibiotics cannot be obtained without a prescription, do not treat all diseases, and can cause resistance and side effects.